Coronavirus disease 2019 (COVID-19): A literature review - Harapan, Harapan; Itoh, Naoya; Yufika, Amanda; Winardi, Wira; Keam, Synat; Te, Haypheng; Megawati, Dewi; Hayati, Zinatul; Wagner, Abram L.; Mudatsir, Mudatsir (Journal of infection and public health, 2020)
In early December 2019, an outbreak of coronavirus disease 2019 (COVID-19), caused by a novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), occurred in Wuhan City, Hubei Province, China. On January 30, 2020 the World Health Organization declared the outbreak as a Public Health Emergency of International Concern. As of February 14, 2020, 49,053 laboratory-confirmed and 1,381 deaths have been reported globally. Perceived risk of acquiring disease has led many governments to institute a variety of control measures. We conducted a literature review of publicly available information to summarize knowledge about the pathogen and the current epidemic. In this literature review, the causative agent, pathogenesis and immune responses, epidemiology, diagnosis, treatment and management of the disease, control and preventions strategies are all reviewed.